A análise econômico-jurídica da arbitragem expedita - Arend, Andréia Propp (Universidade do Vale do Rio dos Sinos, 2018)
Expedited arbitration is an appropriate and private method of conflict resolution, with international origin and progressively adopted in Brazil by virtue of legislative and regulatory permission, to resolve issues of low complexity and low values involved. This study aims to analyze expedited arbitrage from the perspective of the Law & Economics, as a tool to verify transaction and opportunity costs in choosing the procedure to adopt. For this purpose, bibliographic research, data collection and legislative and regulatory analysis were used. The research contributes to the identification of the procedure as a way of accessing companies to arbitration through an excellent cost-benefit relationship, depending on the quantity and quality of the information that the parties are willing to present to each other and to the judge in a short time. As a result, it can be concluded that the Economic-Legal Analysis of Expedited Arbitration can demonstrate that the expedited procedure presents itself as an optimal transaction and opportunity cost reducer, bringing advantages to parties who need a speedy specialized judgment in the causes of low complexity, and it is not recommended to adopt it in multiparty contracts.
Keywords: Arbitragem expedita; Custos de transação; Custos de oportunidade; Precisão da decisão arbitral; Expedited arbitration; Transaction costs; Oportunity costs; Accuracy of arbitration award; ACCNPQ::Ciências Sociais Aplicadas::Direito